Direction of Trade Statistics Yearbook, 2017. (Direction of Trade Statistics; Direction of Trade Statistics, 2017)
This paper discusses those countries that have never reported data by trade partners to the IMF or to the United Nations COMTRADE, estimates are obtained by using directly the corresponding bilateral flow reported by counterpart countries. For example, if country B has never reported trade statistics with a geographical breakdown, but country A has reported imports from country B, then A's data for imports are used to estimate B's exports. Because imports are valued on a cost, insurance, and freight (CIF) basis and exports on a free on board (FOB) basis, the data are adjusted for the cost of freight and insurance. A CIF/FOB factor of 1.06 is currently used. Reported imports CIF are divided by 1.06 (i.e., the CIF/FOB factor) to give partner country estimates of exports FOB. Similarly, reported exports FOB are multiplied by 1.06 to give partner country imports CIF.